Stosowanie środków zabezpieczających wobec sprawców czynów karalnych popełnianych w ramach poszczególnych form stadialnych i zjawiskowych - Góralski, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The paper states that provisions of the Criminal Code of 1997 do not expressly determine whether preventive measures might be imposed on instigators and accessories in the commission of acrime. The same refers to persons who prepared or attempted to commit a crime.Based on the rules of interpretation, the author of the paper prepared a juxtaposition of the arguments for and against application of preventive measures in the particular forms of criminal liability and the particular stages in the commission of a crime.
Keywords: środki zapobiegawcze; etapy popełnienia przestępstwa; formy karalności